ANALISIS PENDAPATAN PENGELOLAAN HUTAN BERSAMA MASYARAKAT (PHBM) TERHADAP PENINGKATAN PEREKONOMIAN - Ripani Maliabarkah; Ilham Adhya; Dede Kosasih (Faculty of Forestry and Environment, Universitas Kuningan, 2022)
One of the factors that determine the success rate of implementing the PHBM program is institutional activity, in this case the institution in question is an active LMDH, namely LMDH which involves the community in every activity implementation. To realize the implementation of the PHBM program in accordance with the objectives. The method used in this research is the interview method by using a questionnaire and the object is LMDH Rimba Raya Lestari farmers, Babakanjawa village. The results of the research on the characteristics of PHBM farmers from mango NTFPs with a profit sharing mechanism of 75% for farmer groups and 25% for Perhutani, the second activity is in the form of mountain coral tourism sharing with a mechanism of 50% for managers and 50% for LMDH Rima Raya Lestari. The income of PHBM farmers in an LMDH group at KPH Majalengka BKPH Majalengka can be seen for their income from corn commodity of IDR 3,562,500 / year, Porang on tuber income of IDR 36,400,000 / year, frog porang of IDR 31,500,000 / year and guava Crystals of 45,000,000/year.Salah satu faktor yang menentukan tingkat keberhasilan pelaksanaan program PHBM adalah kegiatan kelembagaan, dalam hal ini lembaga yang dimaksud adalah LMDH aktif yaitu LMDH yang melibatkan masyarakat dalam setiap pelaksanaan kegiatan. Mewujudkan pelaksanaan program PHBM sesuai dengan tujuan. Metode yang digunakan dalam penelitian ini adalah metode wawancara dengan menggunakan kuesioner dan objek penelitian adalah petani LMDH Rimba Raya Lestari Desa Babakanjawa. Hasil penelitian karakteristik petani PHBM dari HHBK mangga dengan mekanisme bagi hasil 75% untuk kelompok tani dan 25% untuk Perhutani, kegiatan kedua berupa bagi hasil wisata karang gunung dengan mekanisme 50% untuk pengelola dan 50% untuk LMDH Rima Raya Lestari. Pendapatan petani PHBM kelompok LMDH di KPH Majalengka BKPH Majalengka dapat dilihat dari pendapatannya dari komoditi jagung Rp 3.562.500/tahun, Porang pada pendapatan umbi-umbian Rp 36.400.000/tahun, porang kodok Rp 31.500.000/tahun dan jambu kristal 45.000.000/tahun